2020
DOI: 10.3390/mi11080712
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Study of the Effect of Abrasive Grains Orientation and Spacing during Nanogrinding

Abstract: Grinding at the nanometric level can be efficiently employed for the creation of surfaces with ultrahigh precision by removing a few atomic layers from the substrate. However, since measurements at this level are rather difficult, numerical investigation can be conducted in order to reveal the mechanisms of material removal during nanogrinding. In the present study, a Molecular Dynamics model with multiple abrasive grains is developed in order to determine the effect of spacing between the adjacent rows of abr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…According to Xie [ 21 ], the greater the extrusion height, extrusion volume, stiffness and front angle, and the smaller the back angle, main deviation angle and secondary deviation angle, the better the cutting performance of the grinding wheel. Therefore, the geometric characteristics of active abrasive grains on the surface of grinding wheels play an important role in the removal of workpiece materials, grinding force, surface roughness, machining efficiency and surface quality, and the grinding mechanism of active abrasive grains offers valuable insights into the machining characteristics of gear honing [ 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to Xie [ 21 ], the greater the extrusion height, extrusion volume, stiffness and front angle, and the smaller the back angle, main deviation angle and secondary deviation angle, the better the cutting performance of the grinding wheel. Therefore, the geometric characteristics of active abrasive grains on the surface of grinding wheels play an important role in the removal of workpiece materials, grinding force, surface roughness, machining efficiency and surface quality, and the grinding mechanism of active abrasive grains offers valuable insights into the machining characteristics of gear honing [ 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…A characteristic feature that clearly distinguishes ceramic materials from metal materials is their low ductility and low fracture toughness regardless of strength. In ceramics, grinding processes, high-quality machining is possible when the energy consumption of the process is reduced and the gradient of mechanical and thermal load on the workpiece surface in the grinding zone is reduced [1][2][3][4]. This means limiting the formation and propagation of cracks especially near the edge of the workpiece [5].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that meeting these requirements was possible through the use of a new method and new tools. Conclusions came from the resent investigations on the features of abrasive tools [3,8,19,20], process kinematics [21], the influence of the processed material properties on the process results [22][23][24][25][26] and cutting fluid [9,27]. In the assumptions for the new method, the developed methodology of process monitoring [28,29], a thorough analysis of the properties of abrasive tools [30][31][32], and the topography of the treated surfaces [33] were used.…”
Section: Introductionmentioning
confidence: 99%
“…This Special Issue showcases 12 state-of-the-art examples of modeling and simulation in micro- and nano-manufacturing processes. The papers that are published in this Special Issue explore the following micro- and nano-manufacturing processes: laser texturing [ 1 , 2 ], 3D printing [ 3 , 4 ], grinding [ 5 , 6 ], turning [ 7 , 8 ], and electrochemical machining [ 9 , 10 ]. The remaining papers cover lithography-based manufacturing [ 11 ], and micro- and nano-scale design aspects [ 12 ].…”
mentioning
confidence: 99%
“…Manea et al developed an arithmetical model to calculate the nano-scale grinding force required to machine optical glass, and analyzed how processing parameters can be controlled to achieve high surface and subsurface quality [ 5 ]. Karkalos et al focused on molecular dynamics modeling with multiple abrasive grains, to study the effect of spacing between the adjacent rows of abrasive grains and the effect of the rake angle of the abrasive grains [ 6 ]. They evaluated the grinding forces and temperatures, ground surface quality, chip formation, and subsurface damage of the substrate.…”
mentioning
confidence: 99%